Peran Brand Trust Memediasi Pengaruh E-Wom Terhadap Keputusan Pembelian (Studi Pada Rumah Makan Nami Rasa Kabupaten Tabanan) - Putri, Ni Made Siska Namira; Rastini, Ni Made (Syntax Corporation, 2025)
The growth of the current business sector shows an increase in intense competition, especially in the culinary business field. The increasing number of restaurants and eateries in Bali Province has resulted in tighter competition among culinary entrepreneurs. Based on this phenomenon, business actors must have the right business strategy to survive and remain competitive amid the increasingly fierce competition among culinary business players. This study aims to analyze the role of brand trust in mediating the influence of electronic word of mouth (e-WOM) on consumer purchasing decisions. This research was conducted at the Nami Rasa Restaurant, Tabanan Regency with a sample of 100 respondents using a non-probability sampling method with a purposive sampling technique based on respondents who were at high school level, had searched for and read reviews on online platforms about the Nami Rasa Restaurant, and had bought food at the Nami Rasa Restaurant in the last 3 (three) months when this research was conducted.. The data analysis techniques used were descriptive analysis and inferential analysis, including path analysis, Sobel test, and VAF test. The results showed that e-WOM has a positive and significant influence on purchasing decisions. e-WOM also has a positive and significant influence on brand trust. Brand trust has a positive and significant influence on purchasing decisions. Brand trust partially mediates the influence of product quality on purchasing decisions at Nami Rasa Restaurant in Tabanan Regency. The implication of this research can serve as a consideration and input for Nami Rasa Restaurant in improving consumer purchasing decisions by considering the variables of e-WOM and brand trust.